Hypergammaglobulinemia in Hidradenitis Suppurativa Patients: A New Emerging Association - Martora F; Battista T; Giordano A; Potestio L; Megna M (Clinical, Cosmetic and Investigational Dermatology)
Fabrizio Martora,* Teresa Battista,* Antonella Giordano, Luca Potestio, Matteo Megna Dermatology Unit, Department of Clinical Medicine and Surgery, University of Naples Federico II, Naples, Italy*These authors contributed equally to this workCorrespondence: Fabrizio Martora, Section of Dermatology - Department of Clinical Medicine and Surgery, University of Naples Federico II, Via Pansini 5, Napoli, 80131, Italy, Tel +39 - 081 – 7462457, Fax +39 - 081 – 7462442, Email fabriziomartora92@libero.itAbstract: Hypergammaglobulinemia is a sign of B cell and plasma cell hyperactivity marked by elevated levels of gamma globulins, proteins within the gamma fraction of serum electrophoresis, linked to diseases like acute hepatitis, Hodgkin’s lymphoma, autoimmune conditions, and neoplasms. Monoclonal gammopathy of undetermined significance (MGUS) is found in 3.2% of individuals over 50 and 5.3% over 70 due to immunosenescence, the gradual immune decline influenced by chronic infections, malnutrition, hormonal dysregulation, and smoking. This retrospective, single-center observational study explored the association between hypergammaglobulinemia and Hidradenitis Suppurativa (HS) based on sex, age, disease severity (IHS4 score), and Adalimumab treatment. Sixty patients (54% women, 46% men, average age 47) were observed over 12 months. Hypergammaglobulinemia was found in 68% of patients, with the highest prevalence in the 15– 29 age group (80%). It was also associated with increased disease severity, particularly in younger patients, who showed a reduced clinical response to Adalimumab (average HiSCR difference of 25%). While common inflammation markers like CRP and ESR remain essential for HS management, this study highlighted that hypergammaglobulinemia is more prevalent in younger patients with severe forms of HS. Unlike older patients, where immunosenescence can lead to more normal gamma globulin levels, younger patients demonstrated a strong link between chronic inflammation and disease. The findings suggest further investigation is needed to determine whether hypergammaglobulinemia is merely a marker or contributes to HS pathogenesis. If validated, hypergammaglobulinemia could be used to monitor disease progression and customize treatments. In conclusion, integrating immunological assessments into HS management could improve patient outcomes, particularly in younger demographics. With larger studies, hypergammaglobulinemia might be considered a predictive factor for HS, especially for severe or treatment-resistant cases.Keywords: hidradenitis suppurativa, hypergammaglobulinemia, immunosenescence